2018
DOI: 10.4314/jae.v22i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Constraints to women farmers’ entrepreneurial development in Nasarawa State, Nigeria

Abstract: This study examined the entrepreneurial competencies among women farmers in Nasarawa State, Nigeria. Specifically, this paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
7
1
1
Order By: Relevance
“…The average monthly income of the respondents was 50,136.13Naira.This indicates that food marketing is a viable means of livelihoods as the average monthly income of the respondents is above the new national minimum wage of 30,000 naira in Nigeria. This result is contrary to the findings of Kagbu (2018) who reported that average monthly income of women farmers in Nasarawa State, Nigeria was 17,396.62 Naira. The average years of experience of the respondents was 5.7 years.…”
Section: Resultscontrasting
confidence: 97%
“…The average monthly income of the respondents was 50,136.13Naira.This indicates that food marketing is a viable means of livelihoods as the average monthly income of the respondents is above the new national minimum wage of 30,000 naira in Nigeria. This result is contrary to the findings of Kagbu (2018) who reported that average monthly income of women farmers in Nasarawa State, Nigeria was 17,396.62 Naira. The average years of experience of the respondents was 5.7 years.…”
Section: Resultscontrasting
confidence: 97%
“…Komitmen dalam menjalankan bisnis akan membentuk rasa tanggung jawab pada diri petani untuk memberikan produk dan jasa yang terbaik guna memenuhi permintaan konsumen (Kagbu 2018 threats, sehingga menghasilkan strategi WT Total skor dalam matriks evaluasi faktor internal dan eksternal miliki range 1 sampai 4 dengan rata-rata 2,5. Total skor tertimbang di bawah 2,5 mencirikan organisasi yang lemah secara internal, sedangkan skor di atas 2,5 menunjukkan posisi internal yang kuat (David 2017).…”
Section: Pendahuluanunclassified
“…Concerted efforts are required to support female entrepreneurs in making better economic choices to be able to transform their potential endeavours for tangible economic gains, maintains the OECD (1997) (in Kagbu, 2018: 45). Entrepreneurship therefore represents an appropriate opportunity for women all over the world, as entrepreneurship responds flexibly to entry, change and innovation.…”
Section: Overview Of Enterprise Clustering In the Informal Sectormentioning
confidence: 99%
“…This potential has not yet been realized optimally in most developing countries as a large number of women work in informal sectors but their contributions are subject to constraints and abilities to upgrade production continuously. These include poor access to market information, technology and finance, support services, policy and regulatory environments (UNIDO, 2001 in Kagbu, 2018: 45).…”
Section: Overview Of Enterprise Clustering In the Informal Sectormentioning
confidence: 99%
See 1 more Smart Citation